Recent Developments in the Treatment of Pancreatic Cancer - Paulino, Jorge (2023)
Pancreatic duct adenocarcinoma is currently the sixth-leading cause of cancer death worldwide and the fourth in Europe, with a continuous increase in annual lethality in Portugal during the last two decades. Surgical en-bloc resection of the tumor with microscopic-negative margins and an adequate lymphadenectomy is the only possibility of long-term survival. As this type of cancer is a systemic disease, there is a high rate of recurrence even after curative resection, turning systemic therapy the core of its management, mostly based on chemotherapy. Neoadjuvant strategies for nonmetastatic disease showed significant improvement in overall survival compared with upfront surgery, namely in borderline resectable disease. Moreover, these strategies provided downstaging in several situations allowing R0 resections. Under these new oncologic strategies, several recent surgical issues were introduced, namely more aggressive vascular resections and even tumor resections in oligometastatic disease. This review revisits the state-of-the-art of surgical and oncological interventions in pancreatic duct adenocarcinoma and highlights recent advances in the field aiming to achieve higher survival rates.